Computing Irregularity Indices for Probabilistic Neural Network - Kang, Shunguang; Chu, Yu-Ming; Virk, Abaid ur Rehman; Nazeer, Waqas; Jia, Jia (Frontiers in Physics, 2020)
A topological index (TI) is a quantity expressed as a number that help us to catch symmetry of network. With the help of quantitative structure property relationship (QSPR), we can guess physical and chemical properties of several networks. A neural network is a computer system based on the nerve system. There are numerous uses of these systems in different fields of studies but their most critical use to date is in Neurochemistry. In this paper, we will discuss thirteen irregularity indices for probabilistic neural networks (PNN).